2016
DOI: 10.1103/physrevlett.117.070601
|View full text |Cite
|
Sign up to set email alerts
|

Entropy Production of Nanosystems with Time Scale Separation

Abstract: Energy flows in biomolecular motors and machines are vital to their function. Yet experimental observations are often limited to a small subset of variables that participate in energy transport and dissipation. Here we show, through a solvable Langevin model, that the seemingly hidden entropy production is measurable through the violation spectrum of the fluctuation-response relation of a slow observable. For general Markov systems with time scale separation, we prove that the violation spectrum exhibits a cha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 36 publications
5
43
0
Order By: Relevance
“…With this approach, it was shown how the entropy production obtained from the mesoscopic dynamics, gives a lower bound on the total rate of entropy production. Interestingly, in systems characterized by a large separation of timescales [205] where only the slow variables are monitored, the hidden entropy production arising from the coupling between slow and fast degrees of freedom, can be recovered using Eq. (13).…”
Section: Entropy Production and Stochastic Thermodynamicsmentioning
confidence: 99%
“…With this approach, it was shown how the entropy production obtained from the mesoscopic dynamics, gives a lower bound on the total rate of entropy production. Interestingly, in systems characterized by a large separation of timescales [205] where only the slow variables are monitored, the hidden entropy production arising from the coupling between slow and fast degrees of freedom, can be recovered using Eq. (13).…”
Section: Entropy Production and Stochastic Thermodynamicsmentioning
confidence: 99%
“…The authors of Ref. [42] showed that systems subject to fast drivings display a violation of the fluctuationresponse relation and evaluated its typical shape in the space of frequencies for large time-scale separations. Such violation of the fluctuation response relation is known to be linked to entropy production for Langevin systems by the Harada-Sasa equality [93].…”
Section: Entropy For Block-diagonal Dynamicsmentioning
confidence: 99%
“…Without loss of generality, we set the stationary activity a j u to zero. The activity response function R a is a property of the intracellular molecular network, which can be computed for specific models 38,39 or measured directly in single-cell experiments 3,4,19,40 . In general, R a may depend on the ambient signal level s of the cell.…”
Section: Resultsmentioning
confidence: 99%
“…1 typically follows a dissipative dynamics such as Equation (1). When the medium is close to thermal equilibrium, the Fluctuation-Dissipation Theorem (FDT) relates the imaginary componentR s of the signal responseR s to its spontaneous fluctuationC s induced by thermal noise 38,39,47 : 2TR s (ω) = ωC s (ω), whereC s (ω) = |s(ω)| 2 u is the spectral amplitude of the signal, and T is the temperature. This relation de-mandsR s (ω) to be positive at all frequencies.…”
Section: Resultsmentioning
confidence: 99%